PROSTATE BIOPSIES AND ITS ASSOCIATION WITH PROSTATE SPECIFIC ANTIGEN IN PATIENT ATTENDING BIRAT MEDICAL COLLEGE TEACHING HOSPITAL - Sinha , Amrita; Upadhyaya , Santosh; Singh , Mrinalini; Kafle , Neeta (Journal of Chitwan Medical College, 2022)
Background: Prostate cancer is the most common malignant tumor in men over the age of 65 years. Most frequently encountered diseases of the prostate are benign prostatic hyperplasia, prostatitis and carcinoma. Prostate specific antigen is a tumour marker and is expressed by both normal and neoplastic prostate tissue. This study was done to determine the association between histopathological diagnosis in prostatic biopsy and serum prostatic specific antigen level. Methods: This was a hospital based cross sectional study carried out in the Department of Pathology, Birat Medical College from February 15, 2020 to October15, 2020. All consecutive patients attending the pathology department with prostate biopsy and serum PSA level were included in the study. Histopathological examination was done and its association with serum prostatic specific antigen level was done. Results: In the biopsy findings, Benign Prostatic Hyperplasia (BPH)was the most common case seen in 41 (48.8%) cases out of 84 cases. Majority of benign cases (BPH and BPH with prostatitis) were seen in the PSA range of 0-7ng/ml. Maximum cases of adenocarcinoma were seen in the range of >20ng/ml. Chi-Square test showed a value of 5.89 while P value was <0.01 indicating that the increasing serum PSA level is associated with higher chance of adenocarcinoma. Conclusions: PSA is a specific marker for prostatic tissue. It can be raised in benign lesions of the prostate due to membrane disruption. However, an increased PSA level above 20 ng/ml increases the chance of detecting malignant lesions.